Design and Simulation of a Z-Source Inverter for Electrical Vehicle Application - AIYYAPPAN, VENU PRASAD (2018)
This proposed project will cover the designing and simulation of a Z-Source inverter specifically to be used in the application of a electrical vehicle. Further performance analysis will be carried out and controlling methods will be implemented on the circuit to evaluate to verify its feasibility in said application.